2017
DOI: 10.1007/s12010-017-2400-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Ribonucleotide Reductase from Cordyceps militaris Expressed in Escherichia coli

Abstract: Cordyceps militaris produces cordycepin (3'-deoxyadenosine), which has various activities, including anti-oxidant, anti-tumoral, anti-viral, and anti-inflammatory. Ribonucleotide reductase (RNR) seems to be a candidate to produce cordycepin in C. militaris because RNR catalyzes the reduction of nucleotides to 2'-deoxynucleotides, whose structures are similar to that of cordycepin. However, the role of RNR has not been confirmed yet. In this study, complementary DNAs (cDNAs) of C. militaris RNR (CmRNR) large an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In earlier studies, cordycepin was polymerized via 3′-deoxyribose and adenine using a glycosidic bond ( Kredich and Guarino, 1961 ). However, adenosine can also be used as the precursor of cordycepin synthesis and produces cordycepin through multiple enzymes such as adenylate kinase (ADEK), ferritin/ribonucleotide reductase-like protein (RNR), 5’-nucleotidase (NT5E), adenosine nucleosidase, oxidoreductase domain-containing protein (Cns1), and phosphoribosyl-aminoimidazole-succinocarboxamide synthase (Cns2) ( Suhadolnik and Cory, 1964 ; Lennon and Suhadolnik, 1976 ; Kato et al, 2017 ; Liu et al, 2018 ). In addition, a mutation of CmWC-1 repressed cordycepin biosynthesis and fruiting body development ( Yang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, cordycepin was polymerized via 3′-deoxyribose and adenine using a glycosidic bond ( Kredich and Guarino, 1961 ). However, adenosine can also be used as the precursor of cordycepin synthesis and produces cordycepin through multiple enzymes such as adenylate kinase (ADEK), ferritin/ribonucleotide reductase-like protein (RNR), 5’-nucleotidase (NT5E), adenosine nucleosidase, oxidoreductase domain-containing protein (Cns1), and phosphoribosyl-aminoimidazole-succinocarboxamide synthase (Cns2) ( Suhadolnik and Cory, 1964 ; Lennon and Suhadolnik, 1976 ; Kato et al, 2017 ; Liu et al, 2018 ). In addition, a mutation of CmWC-1 repressed cordycepin biosynthesis and fruiting body development ( Yang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the mechanisms of cordycepin synthesis and LAB fermentation has not yet been elucidated. However, the production of cordycepin through lactic acid fermentation may be similar to the synthesis of 2-deoxrtivonucleotides from adenosine, adenosine monophosphate, or adenosine diphosphate by ribonucleotide reductase [51][52][53]. Recent studies have reported that cordycepin showed anti-viral activity by targeting the spike protein, main protease, and RNAdependent RNA polymerase of viruses [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, according to the similarity to 2′deoxyadenosine biosynthesis, Xiang et al predicted that the biosynthesis of cordycepin may proceed through a reductive mechanism after transcriptome analysis of the O. sinensis fruiting body (Xiang et al, 2014), but they didn't verify the cordycepin biosynthesis pathway. Untill 2017, the recombinant E. coli which expressed CmRNR showed RNR activity on ADP but did not produce 3' -deoxy ADP (Kato et al, 2017), which seemed to deny the participation of RNR in cordycepin biosynthesis in C. militaris. But in 2020, Zhang et al indicated that the RNR consisted of two subunits: a large one (RNRL) and a small one (RNRM), RNRM could regulate the biosynthesis of cordycepin directly via the reduction of adenosine, as demonstrated by overexpressing RNRM in C. militaris (Zhang et al, 2020b).…”
Section: Biosynthesis Of Cordycepinmentioning
confidence: 99%